(untitled) (Dhaka University Journal of Biological Sciences, 2021)
Measuring parental self-efficacy has influenced the children and their environment for reaching optimal development. The current study aimed to adapt the Tool to Measure Parenting Self-Efficacy (TOPSE) scale and to determine its psychometric properties for using in the context of Bangladesh. A total of 180 mothers of children aged 0 to 6 years were conveniently selected for this study. The TOPSE and Rosenberg’s Self-Esteem scale were used as measuring instruments. Collected data were analyzed to determine psychometric properties by using Cronbach’s alpha, Pearson product moment correlation coefficient, item analysis, and factor analysis. TOPSE had acceptable internal consistency (Coefficient alpha=0.89) and test-retest reliability (r=0.96). The convergent validity of TOPSE showed a highly positive correlation (r=0.91) with the Bangla Rosenberg’s Self-Esteem scale. The factor analysis resulted in 4 factors with Eigenvalues > 1, explaining 87% of the variances and the four factors showed Cronbach’s coefficient values ranging from 0.50 to 0.99. TOPSE has reasonably good psychometric properties. Further research may wish to require to see the implication of TOPSE in evaluating parenting programs in Bangladesh. Dhaka Univ. J. Biol. Sci. 30(2): 169-177, 2021 (July)